Hot tapping process analysis on gas distribution pipes online service using Shielded Metal Arc Welding - Budi Prasojo; Yunan Sadli Nasution; Endah Wismawati; Subagio So’im; M. Ari (Journal of Welding Technology, 2022)
In a piping system makes it possible to add branching into an existing piping system. In this research will discuss about installation 12 " branch pipe in to 16” existing pipe. The system should be installed without interrupting the operation of the pipeline to avoid huge losses. Hot-tapping is a technology that works to create branching on the online service pipe condition. Calculation and analysis of the results to ensure the process of hot-tapping absolutely safe to operate. parameters that must be considered include the heat input, the operating pressure during welding hot-tapping process with Shielded Metal Arc Welding, stress that occurs at the branching system. Analysis on split tees must be done because of stress that occurs due to the welding process and the reduction in thickness. Analysis on the plumbing system must be done because of a new branching thus causing new stress. The results of the analysis on split tees and the pipe system is used as a reference-making procedures for implementing hot-tapping. Maximum stress that occurs in the pipes during hot-tapping process is the welding area (22.828 psi). The welding process causes melting partial in the metal pipe so, during welding process (hot-tapping) working pressure should be reduced by 25.27%. The condition of the fluid in the existing pipeline still safe because liquefaction as a result of the welding process does not penetrate to the inner pipe. The new design results in branch pipe eligible to fabricated because stress that occurs is still below the allowable stress values